Investigation of the roughness effect on flow behavior and heat transfer characteristics in microchannels. (April 2015) - Liu, Yangpeng; Xu, Guoqiang; Sun, Jining; Li, Haiwang
Abstract: Experiments were conducted to investigate the flow behavior and heat transfer characteristics in microchannels with various surface roughnesses. In the experiments, six test pieces with various roughnesses were fabricated in the stainless steel panel and divided into three groups. Each panel includes 30 microchannels in parallel with uniform geometrical parameters. Both width and depth of microchannels are 0.4 mm. The relative roughness of surface in the microchannel is from 0.58% to 1.26%. All tests were performed with air. The experiments were completed with the Reynolds number in the ranges of 200–2100. The friction factor, heat transfer coefficient, Nusselt number and thermal performance were analyzed based on the experimental results. Results of experiments showed that the surface roughness in microchannel has a remarkable effect on the performance of flow behavior and heat transfer. Based on the experimental data, the friction factor and the Nusselt number increase with the increasing of the surface relative roughness. At the same time, the effect of roughness in the thermal performances is small within the range of experimental parameters. The results also indicate that the heat flux rarely affects the Nusselt number. In this paper, the corresponding empiric equations for flow resistance and heat transfer characteristics in microchannels were developed.